Dominican Republic : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in the Dominican Republic during 1990-95. In 1990, the authorities began implementing a program of stabilization and structural reform that, in a relatively short time, brought inflation under control, permitted a resumption of growth, and made progress toward a more outward-oriented economy with greater participation of the private sector. Real GDP grew at an average rate of 4 percent during 1991-93. The annual average inflation rate was brought down from more than 50 percent in 1990 to about 5 percent in 1993.